Autentikasi Hadith-Hadith Kitab Al-Nikah Daripada Kitab Bulughul Maram Karya Al-Hafiz Ibn Hajar Al-Asqalani: The Authenticity of Hadith in Al-Hafiz Ibn Hajar Al-Asqalani’s Bulugh Al-Maram: A Study on Kitab al-Nikah - Mohd Muhiden Abd Rahman; Mohd Bakhit Haji Ali (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Falsification of hadiths has spread tremendously among society as the dissemination of fabricated hadiths has been normalised among the public and Islamic and religious scholars. This issue is not a new phenomenon but has been evolving since the hadiths were transmitted orally and developed through writing such as books and so on. It is also a well-known fact that hadith scholarship's contribution via writings includes written materials from the current and past Islamic and religious scholars, including Siamese scholars. This article aims to discover the authenticity of hadiths in ‘Kitab al-Nikah’ from the book of ‘Bulughul Maram min Adillat al-Ahkam’ written by al-Hafiz ibn Hajar (m. 852H). Even though al-Hafiz Ibn Hajar mentioned the majority of the sources for the hadiths, yet there are some hadiths which sources are left unmentioned. He also divided the hadiths into thematic points, although few hadiths have not been categorised under suitable themes. All of the hadiths will be analysed in terms of their authenticity, tanasub and suitability in terms of nikah. In order to identify the status and authenticity of the hadiths, a specific method will be used: takhrij (retrieval) based on the theme of the hadiths. A descriptive method will be used to analyse the hadiths in the tanasub point of view and the suitability of the hadith towards certain themes. The research showed that 86% of the hadiths found in ‘Kitab al-Nikah’ are authentic and based on authorised and muktabar books of hadiths. In addition, 95% of the hadiths chosen were relevant and suitable with the theme of nikah.